Genetic polymorphisms of microRNA machinery genes predict overall survival of esophageal squamous carcinoma - Wang, Cuiju (J Clin Lab Anal, 2017)
BACKGROUND: MicroRNA (miRNA)‐related single nucleotide polymorphisms (miR‐SNPs) in miRNA processing machinery genes are implicated in carcinogenesis, as they change the expression profiles of miRNA. Six miR‐SNPs in miRNA processing machinery genes, including Dicer (rs3742330), RAN (rs14035), XPO5 (rs11077), TNRC6B (rs9623117), GEMIN3 (rs197412), and GEMIN4 (rs2740348), were evaluated for their association with esophageal squamous cell carcinoma (ESCC). METHODS: The miR‐SNP of the miRNA processing genes were genotyped using the polymerase chain reaction‐ligase detection reaction (PCR‐LDR) assay, while the XPO5 expression levels in ESCC tissues were measured by immunochemistry methods. RESULTS: Patients carrying the rs11077 AA allele exhibited a significantly increased lifespan than AC+CC carriers, as determined by univariate and multivariate analyses (relative risk: 2.490; 95% confidence interval [CI]: 1.225‐5.058; P=.012). Furthermore, the rs11077 AA genotype displayed a trend for high XPO5 expression in ESCC tissues by immunochemistry analysis, and these high XPO5 expression levels were also associated with high survival rates among ESCC patients. CONCLUSION: Our results suggested that the miRNA machinery gene expression‐associated miR‐SNPs would modify cancer outcomes; in this light, XPO5 may be an important new target for ESCC therapy.